Quand la concertation produit de l’évitement. La mise en œuvre de Natura 2000 en région Nord-Pas de Calais - Agnès Fortier (Développement Durable et Territoires)
During the last decade, the use of procedure based on debate has known a great development in public action. Debating, discussing, consulting together are now recognized as something necessary and more, essential. Beyond this declaration of intent, it is necessary to admit that consulting together does not stand out. It is not enough to convene many stake-olders around a table to bring in a real debate, a real confrontation of different points of view and knowledge, and a least produce agreement. Through the implementation of a participatory approach to managing biodiversity used in the European Habitats directive, especially in the Nord-Pas de Calais Region, we shall examine difficulties and obstacles to implement this kind of collective action.